In vitro spermatogenesis: In search of fully defined conditions - Kulibin, A. Yu.; Malolina, E. A. (Frontiers in Cell and Developmental Biology, 2023)
A complete reconstruction of spermatogenesis in vitro under fully defined conditions still has not been achieved. However, many techniques have been proposed to get closer to that aim. Here we review the current progress in the field. At first, we describe the most successful technique, the organ culture method, which allows to produce functional haploid cells. However, this method is based on the culturing of intact testis tissue with unknown factors acting inside it. Then we discuss different types of 3D cultures where specific testicular cell populations may be aggregated and the impact of each cell population may be examined. Unfortunately, germ cell development does not proceed further than the pachytene stage of meiosis there, with rare exceptions. Finally, we describe recent studies that focus on germ cells in a conventional adherent cell culture. Such studies thoroughly examine issues with in vitro meiosis and provide insight into the mechanisms of meiotic initiation.